Education and training for the oil and gas industry : case studies in partnership and collaboration - Playfoot, Jim; Andrews, Phil (Owner, Getenergy Ltd.) (San Diego, CA ; Waltham, MA : Elsevier, 2014)
'Education and Training for the Oil and Gas Industry: Case Studies in Partnership and Collaboration explores the way in which global standards in education within the oil and gas industry can be developed and implemented through partnership and collaboration. This volume considers the current political and economic context for this within oil and gas producing countries and maps out key stakeholders, explores current education and training provision, gathers perspectives from industry and from national oil companies and develop a manifesto for education and training in the oil and gas industry globally. The Getenergy Guides crystallizes the lessons and examples of best practice from ten years of interactions and engagements. It offers a blueprint for a unified, universal set of quality standards and collates the tools and techniques necessary to implement these standards in a way that all companies, training providers, educators and governments can embrace'--
Includes index.
Keywords: Oil industries -- Employees -- Training of; Petroleum industry and trade -- Employees -- Training of; Engineers -- Education -- Case studies